Implementing Peace Education In Secondary Schools Of Odisha: Perception Of Stake Holders - Lokanath Mıshra (Sakarya University, 2015)
Peace education is fundamentally a process for engaging people in developing awareness of the causes of conflicts and ways to resolve these in daily life. Education is one of the essential factors that will aid in stopping violence and establishing soc emerged as the consequence of various approaches regarding peace from an educational perspective, is a component of teaching tolerance, sharing and honesty to adults and children. The main purpose of peace education is to encourage students to develop different strategies that would provide social justice, not only in their countries, but also around the world. This paper highlights about the perception of parents and teachers about the concept of peace education and how to implement the peace Education in secondary school